2015
DOI: 10.1002/da.22451
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Long-Term Clinical Outcome of Comorbid Posttraumatic Stress Disorder and Major Depressive Disorder After Electroconvulsive Therapy

Abstract: ECT is associated with a significant reduction of symptoms of PTSD and MDD, as well as reduction in risk of suicidality, cardiovascular, and all-cause mortality in MDD and PTSD, an effect more robust than antidepressant-therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Finally, we note that results of a recent study of ECT in veterans with MDD and PTSD showed a positive effect on both MDD and PTSD symptoms. 21 Thus, the effects of rTMS and ECT appear to be quite different in this population of veterans.…”
Section: Possible Causes Of High Remission Ratesmentioning
confidence: 86%
“…Finally, we note that results of a recent study of ECT in veterans with MDD and PTSD showed a positive effect on both MDD and PTSD symptoms. 21 Thus, the effects of rTMS and ECT appear to be quite different in this population of veterans.…”
Section: Possible Causes Of High Remission Ratesmentioning
confidence: 86%
“…The copyright holder for this preprint this version posted October 13, 2020. ; https://doi.org/10.1101/2020.10.10.20210450 doi: medRxiv preprint effective in those with depression and comorbid PTSD compared with depression only (34), and may be superior to pharmacotherapy only (35). Further research on ECT for PTSD is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ECT is associated with lower overall mortality, as compared with depressed patients receiving psychotropics alone, or no treatment [15]. This has been replicated again in a study by Ahmadi, et al [16], with a mean duration of eight years showing statistically significant risk reduction for all-cause mortality as well as lower mortality due suicide and lower cardiovascular mortality in the ECT group compared to patients who did not receive ECT.…”
Section: Introductionmentioning
confidence: 86%